Conjugated Linoleic Acid Treatment Attenuates Cancerous features in Hepatocellular Carcinoma Cells. (12th September 2022) - Miri-Lavasani, Zohre; Torabi, Shukoofeh; Solhi, Roya; Shokouhian, Bahareh; Afsharian, Parvaneh; Heydari, Zahra; Piryaei, Abbas; Farzaneh, Zahra; Hossein-khannazer, Nikoo; Es, Hamidreza Aboulkheyr; Zahmatkesh, Ensieh; Nussler, Andreas; et al.
Abstract : Background. A growing number of hepatocellular carcinoma (HCC), and recurrence frequency recently have drawn researchers' attention to alternative approaches. The concept of differentiation therapies (DT) relies on inducing differentiation in HCC cells in order to inhibit recurrence and metastasis. Hepatocyte nuclear factor 4 alpha (HNF4 α ) is the key hepatogenesis transcription factor and its upregulation may decrease the invasiveness of cancerous cells by suppressing epithelial-mesenchymal transition (EMT). This study aimed to evaluate the effect of conjugated linoleic acid (CLA) treatment, natural ligand of HNF4 α, on the proliferation, migration, and invasion capacities of HCC cells in vitro. Materials and Method. Sk-Hep-1 and Hep-3B cells were treated with different doses of CLA or BIM5078 [1-(2′ -chloro-5′ -nitrobenzenesulfonyl)−2-methylbenzimidazole], an HNF4 α antagonist. The expression levels of HNF4a and EMT related genes were evaluated and associated to hepatocytic functionalities, migration, and colony formation capacities, as well as to viability and proliferation rate of HCC cells. Results. In both HCC lines, CLA treatment induced HNF4α expression in parallel to significantly decreased EMT marker levels, migration, colony formation capacity, and proliferation rate, whereas BIM5078 treatment resulted in the opposite effects. Moreover, CLA supplementation also upregulated ALB, ZO1, and HNF4 α proteins as well as glycogen storage capacity in the treated HCC cells. Conclusion. CLA treatment can induce a remarkable hepatocytic differentiation in HCC cells and attenuates cancerous features. This could be as a result of HNF4a induction and EMT inhibition.